The Impact of Burnout on Quiet Quitting : A Theoretical Analysis of Literature Studies - Safitri, Noor Laila (Kamil : Journal of Education, 2025)
The phenomenon of Quiet Quitting has gained prominence as a response to burnout caused by excessive workload and workplace stress in modern work environments. Burnout, characterized by physical, mental, and emotional exhaustion, negatively impacts employee productivity and well-being. From an Islamic perspective, principles such as tawazun (balance), justice, and the avoidance of israf (excess) offer valuable solutions to address these issues. This study employs a literature review and hermeneutic analysis of the Qur'an to examine the relationship between burnout and quiet quitting through religious lenses and the potential benefits of Islamic values in fostering a healthy and just workplace culture. The findings suggest that applying Islamic principles related to work boundaries and social justice can help prevent burnout and reduce tendencies toward quiet quitting, thereby enhancing overall productivity and worker well-being